Research of the Process of Obtaining Monocalcium Phosphate from Unconditional Phosphate Raw Materials - Abibulla Anarbayev; Balzhan Kabylbekova; Zhakhongir Khussanov; Bakyt Smailov; Nurlan Anarbaev; Yevgeniy Kulikov (ChemEngineering)
The article presents methods for processing low-grade phosphate raw materials from the Chilisay deposit using a circulation method to produce mineral fertilizers and feed monocalcium phosphate. A study was conducted on the process of obtaining high-quality monocalcium phosphate, and optimal parameters for the decomposition of low-grade phosphate raw materials were determined. Based on the research, it was established that for the decomposition of phosphate raw materials, phosphoric acid with a concentration of 36–42% P2O5 should be used; the recycle phosphoric acid rate should be 540–560% of the stoichiometric amount required for the formation of monocalcium phosphate (MCP); the decomposition temperature should be 95–100 °C; the decomposition duration should be 40–50 min; the filtration temperature of the insoluble residue should be 85–90 °C; the crystallization temperature of MCP should be 40–45 °C; and the crystallization duration should be 85–90 min. For the sulfation of the mother solution and the production of recycle phosphoric acid, sulfuric acid with a concentration of 86–93% H2SO4 should be used; the sulfuric acid rate should be 95–100% of the stoichiometric amount required for the decomposition of dissolved Ca(H2PO4)2. After drying the wet residue, monocalcium phosphate was obtained with the following composition: P2O5—55%, Ca—18.01%, H2O—4.0%, F—0.01%, As—0.004%, Pb—0.002%. The obtained monocalcium phosphate is used in agriculture as a mineral fertilizer and feed monocalcium phosphate.